Securing and optimizing optical transmission in quantum wells using OAM and advanced modulation techniques - Muhammad Ahmad; Zhiping Wang; Ming Fang; Zhixiang Huang; Guoda Xie (Scientific Reports)
Abstract Orbital Angular Momentum (OAM) has gained significant attention in wireless communication, particularly for high-speed, large-capacity optical wireless communication (OWC) systems. However, current optical transmission methods encounter challenges in efficiently transmitting data due to limited OAM mode generation, reduced transmission privacy, and high atmospheric turbulence. The paper proposes an optimized and secure optical transmission in quantum wells to overcome these limitations using OAM and advanced modulation approaches. First of all, this paper proposes an orthogonal frequency division multiplexer (OFDM) with Quadrature amplitude modulation (QAM) and a Spatial Light Modulator (SLM) with Helical Phase Distribution, which enhances the OAM mode generation. After the signal generation process is completed, a hybrid method called Traffic Prediction Assisted with a Spotted Hyena Optimizer (TPAR-SHO) is proposed to analyze traffic in the optical transmission system. The Quantum Well Structure with Injection Locking Synchronization (QWS-ILCS) algorithm is proposed to improve the security of the transmission system. The OFDM with Proportional-Integral-Derivative (OFDM-PID) Controller approach is proposed to safeguard the optical transmission system from atmospheric turbulence. Finally, the Fast Fourier Transform with a Fiber Optical Performance monitoring tool (FFT-FOPM) is proposed for efficient signal processing and comprehensive network monitoring. The simulation results show that the proposed system achieved a low bit error rate (BER) of (17.63%), network throughput of (0.96 Mbps), data integrity rate of (75%), signal quality of (0.3 dB), and blocking probability of (0.03%), which outperforms the state-of-the-art. The results demonstrate that the proposed approach enhances optical transmission networks’ efficiency, reliability, and security.